Synthesis and characterization of double network carbon nanotube hydrogels with calcium bridges’ mechanical properties - Chan, Xunli (2015)
Hydrogels have great potential as soft body tissue replacements. However due to their weak mechanical properties, are unable to fulfil this application. A double network hydrogel (30% hydrogel concentration) of polyethylene glycol diacrylate (PEGDA) and poly acrylic acid (PAA) along with multi-walled carbon nanotube (MWNT) of 1 mg/ml concentration was synthesized to attempt to strengthen the mechanical properties of the hydrogel. Furthermore, the MWNTs were functionalized with carboxyl groups and the hydrogels immersed in dissolved calcium chloride in order to form strong calcium bridges. A single network PEGDA hydrogel with MWNT and calcium was also synthesized for comparison. The single network hydrogel showed an approximate 15% increase in storage modulus, and the double network showed a negligible increase.